Sistem Monitoring Suhu Berbasis Web Dengan Akuisisi Data Melalui Port Paralel PC - Imam Santoso; R. Rizal Isnanto; Achmad Chaerodin (Transmisi: Jurnal Ilmiah Teknik Elektro, 2012)
Many industrial activities need remote monitoring facilities to perform their works. One of monitoring technology implementation is temperature monitoring system application. Temperature value is required in many physical calculation, starting from chemical reaction until machine efficiency. Conventional monitoring system has some weaknesses such as impracticability and data inaccuracy. Therefore, it is required to develop a temperature monitoring system which can be accessed via web using automatic acquisition. The purpose of this Final Project is to make a temperature monitoring system which can be accessed via web using data acquisition via parallel port in the computer (PC). In developing this temperature monitoring system, it uses LM35 temperature sensor as a transducer. Visual Basic 6.0 is used in developing a data acquisition software and Microsoft Access file as a temperature database. PHP is used as a web programming language. System development steps which have been done are literature study, hardware and software design based on literature study, implementation of hardware and application program which has beendesigned, and research to the system.From the research, it can be obtained that temperature data acquisition can be done automatically via parallel port. Data from the acquisition using temperature sensor has an average difference of 0.58°C when it is compared with the thermometer reading. From the system testing, it can be obtained that temperature monitoring can be done in real time. Temperature data searching can be done from the web which has been created. This searching result can be shown in table or temperature chart. Keywords: temperature monitoring system, parallel port, web, PHP, Visual Basic